The effect of the oral iron chelator deferiprone on the liver damage induced by tamoxifen in female rats - Cerná, Pavla; Kotyzová, Dana; Eybl, Vladislav (Hemoglobin, 2011)
Tamoxifen (TAM) is a non-steroidal antiestrogen used in the treatment and prevention of hormone-dependent breast cancer. Tamoxifen therapy may be accompanied with hepatic injury and iron accumulation in this organ. The present study investigates the influence of the effective oral iron chelator, deferiprone (L1), in TAM-induced acute liver injury. Four groups of female Wistar rats were used: I, control; II, TAM; III, TAM+L1; IV, L1. Tamoxifen (75 mg/kg) was administered orally on the first and second day; L1 (50 mg/kg) was administered orally on the first, second and third day of the experiment. On the fourth day, parameters of oxidative state: lipid peroxidation (LP), glutathione (GSH) and catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) activities were estimated in liver homogenates. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), glutamate dehydrogenase (GLDH) levels and iron hepatic content were also evaluated. The TAM-induced oxidative damage was demonstrated by increased LP (52% above controls) and decreased GPx activity (to 92% of controls). The protective effect of L1 was manifested by attenuation of LP (p <0.05) and preserving of GPx activity. The TAM-induced increase of serum ALT and AST activity remained unchanged by L1 treatment. Significant increase of hepatic iron (Fe) level (41% above controls) was found in TAM-treated rats. Hepatic Fe accumulation was completely prevented by L1 treatment.
Keywords: Animals; Female; pyridony; Rats, Wistar; tamoxifen; železo; Enzyme Assays; výsledek terapie; ženské pohlaví; lékové postižení jater; Iron Chelating Agents; Protective Agents; Pyridones; Treatment Outcome; enzymatické testy; peroxidace lipidů; Lipid Peroxidation; Deferiprone; Iron; krysa rodu Rattus; Chemical and Drug Induced Liver Injury; deferipron; Tamoxifen; zvířata; ochranné látky; chelátory železa; Rats; potkani Wistar